2022
DOI: 10.1039/d2ra05048j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of dimethyl phthalate in wastewater via heterogeneous catalytic ozonation process: performances and mechanisms

Abstract: An efficient heterogeneous catalytic ozonation system using CeO2/Al2O3 catalyst was developed to remove dimethyl phthalate (DMP) from wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…According to Wang and Chen [34], the adsorption of organic molecule on the catalyst is critical for catalytic ozonation. Yuan et al [35] also found that the adsorption of organics onto the catalyst was an important step which would have a direct influence on the effectiveness of the heterogeneous catalytic oxidation. Therefore, the adsorption capacity of the catalyst needs to be analyzed.…”
Section: Mechanism Of Rr195 Degradationmentioning
confidence: 99%
“…According to Wang and Chen [34], the adsorption of organic molecule on the catalyst is critical for catalytic ozonation. Yuan et al [35] also found that the adsorption of organics onto the catalyst was an important step which would have a direct influence on the effectiveness of the heterogeneous catalytic oxidation. Therefore, the adsorption capacity of the catalyst needs to be analyzed.…”
Section: Mechanism Of Rr195 Degradationmentioning
confidence: 99%
“…[20] Aluminum oxide (Al 2 O 3 ) containing catalysts have been used to for the dehydrogenation of ethylbenzene to styrene [21,22] and the ozonation of dimethyl phthalate. [23,24] Since both TiO 2 and Al 2 O 3 have been successfully used as catalysts for various phthalates and/or styrene, they have been chosen as metal oxide dopants to be incorporated into PANI in an effort to improve the sorption of these analytes.…”
Section: Introductionmentioning
confidence: 99%